2007
DOI: 10.1063/1.2775048
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of electrical characteristics of TiO2-incorporated HfO2 n-type doped gallium arsenide metal oxide semiconductor capacitor with silicon interface passivation layer

Abstract: Structural approach of TiO2-incorporated HfO2 multimetal dielectric n-type doped gallium arsenide (n-GaAs) metal oxide semiconductor capacitors and their electrical characteristics are investigated. Top TiO2 with bottom HfO2 bilayer dielectric shows excellent C-V characteristics and the lowest hysteresis. Scaling down of this TiO2∕HfO2 dielectric results in substantial reduction in hysteresis and equivalent oxide thickness compared to HfO2 dielectric. Reduced hysteresis is believed to be due to lower trap dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Figure 7 plots the characteristic of J g vs CET or EOT along with the previously published data. 3,5,[13][14][15]38,39 We observed that the Gd 2 O 3 /n-GaAs capacitors through WCP optimization exhibited excellent insulating properties as compared to HfO 2 dielectrics reported on the n-GaAs in combination with Si or Ge interfacial passivation layers. A lower CET of ca.…”
Section: Gaas + As 2 O 3 → Ga 2 O 3 + 4as ͓4͔mentioning
confidence: 80%
“…Figure 7 plots the characteristic of J g vs CET or EOT along with the previously published data. 3,5,[13][14][15]38,39 We observed that the Gd 2 O 3 /n-GaAs capacitors through WCP optimization exhibited excellent insulating properties as compared to HfO 2 dielectrics reported on the n-GaAs in combination with Si or Ge interfacial passivation layers. A lower CET of ca.…”
Section: Gaas + As 2 O 3 → Ga 2 O 3 + 4as ͓4͔mentioning
confidence: 80%